Dalit theology in the twenty-first century : discordant voices, discerning pathways - Kolkata Symposium on "Dalit Theology in the Twenty-first Century" (2008 : Bishop's College); Clarke, Sathianathan; Manchala, Deenabandhu; Peacock, Philip Vinod (New Delhi : Oxford University Press, 2010)
Contributed articles presented at a Kolkata Symposium on "Dalit Theology in the Twenty-first Century" held in January 2008 at Bishop's College, Kolkata.
Includes bibliographical references and index.
Keywords: DALIT; THEOLOGY